Seroprevalence of Hepatitis B and C and HIV Infections and Associated Risk Factors Among Pregnant Women Attending Antenatal Care Unit at Simada Hospital, South Gondar Zone, Northwest Ethiopia. - Tesfaye, Solomon; Abebaw, Tirngo; Bizualem, Endalkachew; Mehabie, Daniel; Alelign, Amir; Pasciu, Valeria (BioMed Research International, 2025)
Hepatitis and human immunodeficiency virus (HIV) are major public health issues in developing countries, including Ethiopia. These viruses can be transmitted from mother to child during birth or through contact with contaminated blood. In many areas of Ethiopia, viral hepatitis and HIV infections are significant health concerns for pregnant women. However, there is limited information about these issues in various parts of the country, particularly in the Amhara Region. Therefore, this study was aimed at determining the prevalence of Hepatitis B virus (HBV), Hepatitis C virus (HCV), and HIV infections and identifies the associated risk factors among pregnant women attending an antenatal care (ANC) unit at Simada Hospital, Amhara Region, Northwest Ethiopia. A hospital‐based cross‐sectional study was conducted on 248 pregnant women from January 2021 to March 2021. Five milliliters of venous blood was collected from each study participant, and serum was tested for Hepatitis B surface antigen (HBsAg), anti‐HCV, and anti‐HIV antibodies using commercially available rapid test kits. A logistic regression analysis was used to identify possible risk factors for the occurrence of hepatitis and HIV infections. The overall seroprevalence of HBV, HCV, and HIV infections was 10 (4%), 5 (2%), and 5 (2%), respectively. Prevalence of coinfection was 1.2% (3/248), 0.4% (1/248), and 0.4% (1/248) for HBV/HCV, HBV/HIV, and HCV/HIV, respectively. History of abortion (adjusted odds ratio (AOR) = 11.028, 95% confidence interval (CI) = 1.671–72.776, p value = 0.013) and a history of blood transfusions (AOR = 11.298, 95%CI = 1.066–119.777, p value = 0.044) were observed to be significantly associated with an increased risk of HBV infections. However, having multiple sexual partners (AOR = 18.819, 95%CI = 1.074–329.680, p value = 0.045) and history of abortion (AOR = 12.550, 95%CI = 1.174–134.202, p value = 0.036) were the only significant predictors of HCV and HIV infection, respectively. In the current study, we found an intermediate prevalence of HBV and HCV in pregnant women. Therefore, continuous screening of pregnant women for the stated viral infections should be performed to minimize the transmission of the viruses to their children.